2007
DOI: 10.1055/s-2007-960499
|View full text |Cite
|
Sign up to set email alerts
|

Altered Postural Regulation of Foot Skin Oxygenation and Blood Flow in Patients with Type 2 Diabetes Mellitus

Abstract: The present study demonstrated the dissociated regulation of skin oxygenation and blood flow in response to leg dependency. Impaired postural vasoconstriction was associated with altered regulation of skin oxygenation probably due to sympathetic vascular dysfunction in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
11
0
2
Order By: Relevance
“…4,42,43 In concordance to these results, we also could not detect significant changes in capillary blood flow in either diabetic patients or in PAOD patients. Iwase et al 31 showed that transcutaneous oxygen pressure (TcPO 2 ) at the dorsal foot in patients with diabetes was reduced compared to healthy controls, whereas skin blood flow did not differ significantly. This is also in agreement with our results as we reported deteriorated cutaneous oxygen saturation with equivalent blood perfusion in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…4,42,43 In concordance to these results, we also could not detect significant changes in capillary blood flow in either diabetic patients or in PAOD patients. Iwase et al 31 showed that transcutaneous oxygen pressure (TcPO 2 ) at the dorsal foot in patients with diabetes was reduced compared to healthy controls, whereas skin blood flow did not differ significantly. This is also in agreement with our results as we reported deteriorated cutaneous oxygen saturation with equivalent blood perfusion in patients with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities may initiate microvascular damage and contribute to the development of foot complications. The impaired veno-arteriolar reflex is found in both type 1 [45] and type 2 diabetes [28,44,46,47]. known that vascular endothelium plays an important role in controlling microvascular tone by synthesizing and releasing several vasodilator substances such as nitric oxide, prostacyclin, and endothelium-derived hyperpolarizing factor, and vasoconstrictor substances such as prostaglandins, angiotensin II, and endothelin [15,48].…”
Section: Local Sympathetic Veno-arteriolar Axon Reflexmentioning
confidence: 99%
“…6 Such a vasoconstriction reflex response is impaired in people with diabetic neuropathy and ulceration. [7][8][9] The reduction or absence of effective precapillary vasoconstriction upon standing will expose the capillary bed to a high hydrostatic load, leading to edema and thickening of the capillary basement membrane. Very few studies have performed a quantitative assessment of the degree of foot swelling that occurs in a diabetic foot.…”
Section: Introductionmentioning
confidence: 99%